Education and Training Management in Increasing the Quality of Professional Competence in Customer Services Entrepreneurs - Pay Paiya; Iim Wasliman; Sofyan Sauri; Hanafiah (Journal of Islamicate Studies, 2021)
The phenomenon of the problem of education and training management in improving the quality of competence in catering service entrepreneurs, against the background of the problems raised, the basic implementation of understanding education and training management in improving the quality of professional competence of catering service entrepreneurs has not been supported by management and training that can improve the quality of competence. Research develops the theory of Food & Brevage. Qualitative research procedures through observation, interviews, documentation and triangulation management. Focus research questions include; 1) Planning; 2) Organizing; 3) Implementation; 4) Supervision; 5) Problems, and; 6) Education and training management solutions in improving the quality of professional competence of catering service entrepreneurs. Research result; 1) Planning, education and training planning in improving the quality of the competence of catering service entrepreneurs are not fundamentally based on a complete understanding of the catering business supported by knowledge, understanding, skills and attitudes in a competent manner in building the profession in catering business activities. held; 2) Organization, is still passive and has not rooted in system development in an effort to build a systematic and educational and training mechanism that builds professional competence in the scope of the catering business; 3) Implementation, not based on potential analysis and development of human resources that support catering business activities so that the increase in professional competence is not clearly measurable and projected in the achievement of improving the quality of professional competence of catering service entrepreneurs; 4) Supervision, has not been optimized in the development of evaluations to build future improvements in the competence of the catering business profession 5) Problems, juridical, administrative and technical understanding in the catering business itself have not been fundamentally understood by catering service entrepreneurs so that in its development it is difficult to build and fundamentally improved knowledge competence, technological developments and understanding attitudes in building effective cooperation between the catering service entrepreneurs themselves; 6) Solutions, understanding the value of learning in knowledge, environmental and social analysis are built and developed as the basis for improving professional competence.